The Devil's Elixir - Hoffmann, E.T.A. (Saga Egmont, 2022)
E.T.A. Hoffmann\'s \'The Devil\'s Elixir\' is a gothic, horror-fantasy novel inspired by Matthew Gregory Lewis\'s novel \'The Monk\'. Medardus is the son of a sinner and is raised in a monastery to atone for his father\'s past. When Medardus succumbs to temptation, he is dragged into a deadly mystery that sees him travel to Rome, pursued by his murderous lookalike. At the Vatican in Rome, the monk\'s only hope for salvation is the beautiful Aurelie but in order to finally discover the truth of the curse that haunts his family, Medardus must evade the sinister powers of the living and the dead. A must-read for fans of the TV adaptations of Umberto Eco\'s \'The Name of the Rose\' or Rumer Godden\'s \'Black Narcissus\'. E.T.A Hoffmann was a German author of romance, fantasy, and gothic horror, and was highly influential on the Romantic Movement. He is perhaps best known for writing the novella \'The Nutcracker and the Mouse King\' which was the inspiration for Tchaikovsky\'s ballet \'The Nutcracker\'.